2020
DOI: 10.3390/ijms21124406
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PPARα during Experimental Left Ventricular Hypertrophy is Critically Dependent on Nox2 NADPH Oxidase Signalling

Abstract: Pressure overload-induced left ventricular hypertrophy (LVH) is initially adaptive but ultimately promotes systolic dysfunction and chronic heart failure. Whilst underlying pathways are incompletely understood, increased reactive oxygen species generation from Nox2 NADPH oxidases, and metabolic remodelling, largely driven by PPARα downregulation, are separately implicated. Here, we investigated interaction between the two as a key regulator of LVH using in vitro, in vivo and transcriptomic approaches. Phenylep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Moreover, the above abnormalities were abrogated in NOX2-KO hearts, highlighting NOX2 as a key mediator of obesity-induced cardiac hypertrophy. Although the effect of NOX2-KO on cardiac function was not investigated in this study, but in another study improved cardiac systolic function has been observed in NOX2 -/mice in the setting of pressure overload [15]. It therefore appears that dysregulated NOX2 expression is a common determinant of both obesity-and pressure-induced cardiac hypertrophy.…”
Section: Metabolic Disturbancesmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, the above abnormalities were abrogated in NOX2-KO hearts, highlighting NOX2 as a key mediator of obesity-induced cardiac hypertrophy. Although the effect of NOX2-KO on cardiac function was not investigated in this study, but in another study improved cardiac systolic function has been observed in NOX2 -/mice in the setting of pressure overload [15]. It therefore appears that dysregulated NOX2 expression is a common determinant of both obesity-and pressure-induced cardiac hypertrophy.…”
Section: Metabolic Disturbancesmentioning
confidence: 78%
“…Dysregulated expression of NOX proteins has been proposed to contribute to the development of cardiac hypertrophy and cardiac dysfunction. Consistently, elevated levels of NOX2 have been associated with worsening systolic function by a mechanism involving downregulation of PPARα [15], an effect that could be reversed with PPARα activator fenofibrate or NOX2 inhibitor VAS2870. In the same study, transcriptomic analysis of PPARα -/mice subjected to pressure overload revealed alterations in oxidative stress and inflammatory pathways that overlapped with wild-type mice (also subjected to pressure overload), while NOX2 -/mice subjected to pressure overload exhibited minimal changes in these pathways.…”
Section: Mediators Of Oxidative Stress Ros Generating Enzymesmentioning
confidence: 84%
“…In hypertensive rats treated with the PPARα agonist medium-chain triglyceride tricaprylin, PPARα activation reduced cardiac oxidative stress without affecting blood pressure [140]. More recently, Harvey and colleagues showed that phenylephrine-induced hypertrophy in H9c2 cardiomyocytes reduces PPARα expression while increasing NOX2 expression and activity [141]. In line with this finding, NOX2 expression was upregulated in PPARα-null mice subjected to transverse aortic constriction (TAC), suggesting that NOX2 signaling initiates PPARα downregulation during cardiac hypertrophy.…”
Section: Pparαmentioning
confidence: 89%
“…Numerous studies ( Zhao et al, 2017 ) have reported the beneficial effect of activation of the PPARα signal on the development of cardiac hypertrophy, which may be attributed to its regulation of myocardial function and energy metabolism through modulating fatty acid oxidation. Hrvey ( Harvey et al, 2020 ) reported that Nox2 was a key signaling molecule in the pathological reaction of PPARα down-regulation leading to cardiac hypertrophy, which proved that the molecular mechanism of PPARα in cardiac hypertrophy from the negative side. In cardiac hypertrophy, the overexpression of PPARα in cardiac tissue can mediate the p53/GSK3β signaling pathway to significantly improve myocardial energy deficiency and cardiac function, which also supports the important role of PPARα in the pathological process of cardiac hypertrophy ( Rana et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%